Unpacking the Merits and Demerits of Electoral Coalitions in South African Metro-Municipalities from 2016-2019 - Nyawo Gumede; Dominique Emmanuel Uwizeyimana; Alouis Chilunjika (PanAfrican Journal of Governance and Development)
The collapse of colonialism and apartheid marked the emergence of a new political culture of pluralism and democratic political participation in South Africa, which heralded a shift in political attitudes, voter behavior, and political socialization trends in post-1994 South Africa. This has seen polyarchy/pluralism playing a pivotal role in creating politically conducive grounds for coalitions in South African municipalities. In light of this, the study examined the municipal electoral coalition trajectory and unpacked the merits and demerits of electoral coalitions in South African metro municipalities from 2016 to 2019. The study relied on the qualitative research paradigm where purposively selected written documents such as journal articles, council meeting minutes, party manifestoes, and local government reports, among others, were used to collect data. The data were then analyzed using thematic analysis and cross-case analysis. The study alluded to the collapse of the African National Congress (ANC) political hegemony, the fading liberation nostalgia, the rise of new smaller parties, the emergence of popular parties, the disintegration of the liberation movement, power struggles in the liberation movement, and bad governance as catalytic factors for the emergence of coalitions in the South African Metro-municipality elections. The study concluded that coalitions bring opportunities by creating a large resource base for coalition partners, promoting democratic consolidation and state governability. However, coalition partners generally feel compromised by changes in the principles to accommodate other parties with different ideologies. To improve coalition stability and effectiveness, the study recommends that political parties should create explicit coalition agreements, organized dispute resolution procedures, and policy alignment plans.